Spatial and Temporal Distribution Pattern of Pre-Mining Grouting-Induced Microseismicity and Prediction of Water Inrush - Ermeng Zhang; Qifeng Jia; Zhaoxing Liu; Zhenhua Li; Yu Fei (Applied Sciences)
Pre-mining grouting is an effective means to prevent mine water inrush, while the microseismicity information induced by pre-mining grouting is often ignored. This paper proposes a novel method to predict the danger of mine floor water inrush based on pre-mining grouting-induced microseismicity (PMGIM). The mechanical mechanism and characteristics of PMGIM are explored through mechanical analysis and numerical simulation. Taking 182602 working face in Wutongzhuang coal mine as a case study, the temporal and spatial distribution law of PMGIM is analyzed, and the connection between the grouting process and microseismic energy is established. Based on the PMGIM information, Moran’s index is used for the prediction of water inrush possibility, and the validity of the method is verified by electric monitoring.